2014
DOI: 10.1111/ahg.12084
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Novel Frameshift Mutation ofMYO6as the Cause of Autosomal Dominant Nonsyndromic Hearing Loss in a Chinese Family

Abstract: SummaryAutosomal dominant types of nonsyndromic hearing loss (ADNSHL) are typically postlingual in onset and progressive. High genetic heterogeneity, late onset age, and possible confounding due to nongenetic factors hinder the timely molecular diagnoses for most patients. In this study, exome sequencing was applied to investigate a large Chinese family segregating ADNSHL in which we initially failed to find strong evidence of linkage to any locus by whole-genome linkage analysis. Two affected family members w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…As described earlier in the Results, various audiogram configurations existed among the Korean DFNA22 patients. Interestingly, SB60–107 (M/14) in the present study (Figure B) and two affected members (F/35 and M/38) from the Chinese study demonstrated strikingly asymmetric HL, which was not observed in the Caucasian populations. This might be a phenomenon specifically found in East Asian DFNA22 cohorts.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…As described earlier in the Results, various audiogram configurations existed among the Korean DFNA22 patients. Interestingly, SB60–107 (M/14) in the present study (Figure B) and two affected members (F/35 and M/38) from the Chinese study demonstrated strikingly asymmetric HL, which was not observed in the Caucasian populations. This might be a phenomenon specifically found in East Asian DFNA22 cohorts.…”
Section: Discussioncontrasting
confidence: 49%
“…[8][9][10][11][12][13][14][15][16][17][18] Hereditary deafness related to MYO6 captures the interest of both clinicians and researchers because it can be either an autosomal dominant (AD)-or autosomal recessive (AR)-inherited disease, representing a wide spectrum of clinical phenotypes in accordance with the studies mentioned above. 5,6,[8][9][10][11][12][13][14][15][16][17][18] Moreover, MYO6 was found to significantly contribute to AD-inherited genetic hearing loss (HL) in the Korean deaf populations, with five novel variants being reported. 8,12 Although MYO6 is a well-known and widespread deafness gene reported in more than 10 countries, its diverse clinical features make it difficult to produce a set guideline for counselling patients (as well as their family) with MYO6 variants.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations